Il pesciolino argentato. Viaggio alla scoperta del mare dell'Antartide. - PISANO, EVA; E. CALAMELA; C. CATALDO; C. FUCÀ; S. GIODA; M. GALLERI (2013)
Ross and Sesi are two tiny Antarctic silverfish, waiting to come to life in the midst of the Antarctic Sea ice. After hatching from small eggs they go out on unravelling journeys across the sea and grow up in a fantastic environment inhabited by wonderful creatures and dangerous predators. Children willing to know their story are invited to follow Ross and Sesi in the journey of their life cycle, and to participate in the discovery experience of Antarctic marine life. In this the children book updated scientific information, that is the life of the Antarctic fish, Pleuragramma antarcticum, and its particular relationship with sea ice cover, is translated into fancy graphics by creative artists, in order to reach a large audience of very young readers and their not specialized parents. Both graphics and copywriting are set with rigorous attention to the educational message in polar scientific issues and to gender equality.